Between Violence, Vulnerability, Resilience and Resistance: Arab Television News on the Experiences of Syrian Women during the Syrian Conflict - El Zein, Rand (Critical Studies in Media and Communication, 2021)
Cover -- Contents -- List of Tables -- Acknowledgements -- 1. Introduction -- 1.1 Context and Significance -- 1.2 A Brief History of Television News in the Arab World -- 1.3 The Syrian Conflict as a Case Study -- 1.4 Structure of the Book -- 2. Theoretical Framework -- 2.1 Vulnerability, Resistance, and the Dependency on Infrastructure -- 2.2 Power and Different Modes of Violence -- 2.3 Defining Resilience in Neoliberal Times -- 2.4 Resistance, Agency, and the Non‐liberatory Subject -- 3. Methodology -- 3.1 Perspective on Language and Discourse -- 3.2 A Critical Approach to Discourse Analysis -- 3.3 Units of Analysis -- 3.3.1 The Sample Selection -- 3.3.2 The Selection of Dominant Themes -- 3.3.3 The Analysis Process -- 3.4 Methodological Questions on Agency and Points of Reversibility -- 3.5 Methodological Reflections -- 4. Arab Television News Coverage of Former Female Syrian Prisoners in Exile: -- 4.1 Introduction -- 4.2 Research Data -- 4.3 Analysis -- 4.3.1 Imprisonment, Sexual Assault, and Controlled Mobility -- 4.3.2 From Being Shamed to Being Silenced -- 4.4 Conclusion -- 5. Rethinking the Relationship between Child Marriage and Failed Infrastructure during the Syrian Conflict -- 5.1 Introduction -- 5.2 Research Data -- 5.3 Analysis -- 5.3.1 Child Marriage -- 5.3.2 Failed Infrastructure -- 5.4 Conclusion -- 6. Displaced Syrian Women at Work: -- 6.1 Introduction -- 6.2 Research Data -- 6.3 Analysis -- 6.3.1 Talking to Good Resilient Subjects: Displaced Syrian Women Erasing the Past or Painting it through their Work -- 6.3.2 Training the Good Resilient Subject: A Survey of News Reports on Displaced Syrian Women Participating in Vocational and Cash‐for-Work Programs and other blue‐collar Jobs -- 6.4 The Notion of Resilience in a Humanitarian Discourse -- 6.5 Conclusion -- 7. 'Mothers of the Nation': -- 7.1 Introduction -- 7.2 Research Data.